Fault diagnosis for descriptor systems by equivalent transformations ⁎. Issue 24 (2018) - Villanueva, A.; Verde, C.
Abstract: This paper presents an algorithm to obtain redundant relations of a large-scale descriptor systems by using structural analysis tools and the concept of equivalence classes. As a case study, a combined cycle power plant (CCPP) is considered with a nonlinear model described by 37 algebraic and dynamic equations where faults are assumed in some process valves. The main advantage of this proposal is the reduction of possible constraints to generate residuals for decentralized descriptor subsystems by using observers and redundant relations; furthermore, insensitivity to a particular fault set is achieved.